(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2015)
Aflatoxin B1 (AFB1), ochratoxin A (OTA) and zearalenone (ZEA) are widespread mycotoxins with carcinogenic properties, contaminating feed and food. In this study the apoptosis-inducing effect of AFB1, OTA and ZEA combination at concentrations close to the natural contamination, in rat hepatocytes after 15, 30 and 60 days treatment in vivo is presented.